دراسة إمکانیة استثمار قیر العیون الکبریتیة فی منطقة هیتلإغراض البناء والإنشاء - nan, nan; nan, nan; nan, nan (Iraqi Journal of Civil Engineering, 2007)
Extracted asphalt from the sulphate asphalt springs in Heet area was prepared to study its properties and its also involve the study of UV and IR spectra of the natural samples and compared to the spectra of similar petroleum samples taken from Al-DORA Refinery .The study shows that the properties of natural asphalt have a great similitude with the asphalt samples resulting from refining Iraqi petroleum. Analysis of UV and IR for the asphalt sample show the existence of heavy organic compounds, that’s found in asphalt extracted from refineries that used for building and construction and for road pavements.